Youth Labor Skill Training in Nepal - Raju, Dhushyanth (World Bank, Washington, DC, 2018)
Training is one of the main ways that the Nepal government intervenes in the labor market. This descriptive study documents patterns, trends, correlates, and the labor market effects of formal off-the-job training of youth, based on national household survey data. Training rates in Nepal tend to be higher than in other South Asian countries. Within the country, rates are higher for traditionally advantaged groups. While both short- and long-term training programs are available, most programs are short-term. Training is associated with a higher likelihood of employment, wagework, and nonfarm work for women but not for men. Training does not appear to be associated with wage earnings for either gender. Interest in training runs high, especially among traditionally disadvantaged groups, and among those who are currently employed or have previously obtained training. Little rigorous evidence is available for Nepal to inform the extent and nature of public intervention in the training market. The study concludes by offering suggestions for future, policy relevant research.